Pengaruh Ukuran Perusahaan, Kepemilikan Institusional dan Leverage terhadap Pengungkapan Emisi Karbon - Rosita, Vivi Mella; Purnamawati, Indah; Mulyono, Resha Dwi Ayu Pangesti (Politeknik Negeri Jember, 2024)
Unpredictable global warming is still an environmental issue that is often discussed in most countries including Indonesia. Companies must voluntarily disclose carbon emissions in order to gain the trust of investors and potential investors and increase company profits. This study aims to test and analyze the effect of company size, institutional ownership, and leverage on carbon emission disclosure in energy sector and industrial sector companies listed on the Indonesia Stock Exchange in 2020-2022. The sample consisted of 42 companies using a purposive sampling method, while the data analysis method used multiple linear regression analysis. The results showed that company size has a significant positive effect on carbon emission disclosure, while institutional ownership and leverage have no effect on carbon emission disclosure.